Use of Participatory Notes in Indian Equity Markets and Recent Regulatory Changes - Singh, Manmohan (IMF Working Papers; Working Paper ;, 2007)
This paper focuses on the use of participatory notes (PNs) by foreign investors, as a conduit for portfolio flows into Indian equity markets for more than a decade. The broadening of India's foreign investor base, in recent years, has a bias towards hedge funds/unregistered foreign investors who invest primarily via PNs. While tax arbitrage via capital gains tax has almost disappeared since July 2004, it is intriguing to note that since then the demand for PNs has actually increased. The paper suggests some reasons for the continuation of a buoyant market in PNs, and explains the possible impact from the recent regulatory changes.